An Analysis of Appraisal in Selected Beauty Vloggers’ YouTube Videos - Indah Utami Chaerunnisah (Yayasan Literasi Sains Indonesia, 2023)
This research aims to describe and analyze the use of appraisal in selected beauty vloggers’ YouTube videos. It particularly focuses on revealing the types and frequencies of attitudinal appraisal applied in the videos. This study is a descriptive qualitative research which tries to give an in-depth description and analysis of the subject. The data in this study were sentences taken from four beauty vloggers’ videos which are Jeffree Star, Nikkie Tutorials, James Charles and Tati. The researcher gathered the data by first watching the videos, making a transcript of the videos, and watching it more to ensure the accuracy of the transcript. To analyze the data, the researcher applies appraisal theory by Martin and White especially their classification of attitude in appraisal which are appreciation, judgement and affect. This research reveals that there are 416 utterances which applied attitudinal appraisal in the beauty vloggers’ videos. From those utterances, the most dominant type is appreciation with 288 utterances, the second most frequent is affect with 104 utterances and the least applied is judgement with only 24 utterances. The beauty vlogger who most frequently applied attitude is Nikkie Tutorials with a total of 124 utterances, followed by James Charles in the second place with 112 utterances, Tati 95 utterances and Jeffree star in the last position with 85 utterances.